Resistance to triazole fungicides in Pyricularia species is associated with invasive plants from wheat fields in Brazil - Dorigan, Adriano Francis; Carvalho, Giselle De; Poloni, Nadia Maria; Negrisoli, Matheus Mereb; Maciel, João Leodato Nunes; Ceresini, Paulo Cezar (Editora da Universidade Estadual de Maringá - EDUEM, 2019)
ABSTRACT. Triazole fungicides have not been effective for managing the wheat blast disease in Brazil. A broad analysis across six geographical populations of Pyricularia graminis-tritici in central-southern Brazil indicated a high level of resistance to triazole fungicides. Since P. graminis-tritici is also associated with others poaceous species, here, we analyzed whether triazole-resistant isolates of the blast pathogen could be recovered from other poaceous hosts that are invasive of sprayed wheat fields. In addition to P. graminis-tritici (Pygt), we also evaluated the levels of sensitivity of three other grass-associated blast pathogens, which included P. grisea (Pg), P. pennisetigena (Pp), and P. urashimae (Pu). Resistance to the triazole fungicides tebuconazole and epoxiconazole was assessed phenotypically based on EC50 values and molecularly by analysis of the presence of mutations in the CYP51A gene, which encodes for the target enzyme 14-alpha-demethylase. We detected triazole-resistant Pyricularia spp. (Pg, Pp, Pu and Pygt) that is associated with Avena sativa, Cenchrus echinatus, Chloris distichophylla, Cynodon sp., Digitaria horizontalis, D. sanguinalis, Panicum maximum or Urochloa spp. The major outcome from our study was the evidence that invasive poaceous species from wheat fields could be an important source of triazole resistant fungal inoculum for the initial phases of the wheat blast epidemics.
Keywords: blast disease; CYP51A gene; sterol demethylation inhibitor (DMI) fungicides; epoxiconazole; tebuconazole